2018
DOI: 10.1590/1806-93042018000400007
|View full text |Cite
|
Sign up to set email alerts
|

Profile of infected pregnant women and children exposed to HIV at a specialized service in the South of Brazil

Abstract: Objectives: to characterize the social and clinical profile of pregnant women infected with HIV, the factors associated to the prevention of vertical transmission, and to analyze the quality of the information available in the SINAN notification forms and clinical records of infected pregnant women and children exposed to HIV in a specialized service in the countryside of Rio Grande do Sul. Methods: retrospective documentary study conducted from medical records of 110 HIV mothers and their children born betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
1
4
0
1
Order By: Relevance
“…However, there is a larger proportion of women aged 30 and older, consistent with findings from other Brazilian studies. 19,24,25 This, coupled with the fact that 58.1% of pregnant women received their HIV diagnosis before prenatal care, suggests that WLHIV may choose motherhood with the aim of preventing MTCT. 4,26 The analysis of prenatal care and childbirth revealed that 92.8% of pregnant WLHIV in border areas received prenatal care, a lower proportion compared to national data reported in maternity hospitals.…”
Section: Discussion and Con Clus I On Smentioning
confidence: 99%
“…However, there is a larger proportion of women aged 30 and older, consistent with findings from other Brazilian studies. 19,24,25 This, coupled with the fact that 58.1% of pregnant women received their HIV diagnosis before prenatal care, suggests that WLHIV may choose motherhood with the aim of preventing MTCT. 4,26 The analysis of prenatal care and childbirth revealed that 92.8% of pregnant WLHIV in border areas received prenatal care, a lower proportion compared to national data reported in maternity hospitals.…”
Section: Discussion and Con Clus I On Smentioning
confidence: 99%
“…Las características sociales que se presentaban en las embarazadas seropositivas provenientes de Brasil muestran que aquellas que tienen un menor nivel socioeconómico y de escolaridad presentan mayor riesgo de infección fetal y mayores efectos adversos que las embarazadas seropositivas con mejores recursos económicos y educacionales 6,7 . Por otra parte, un tercio de las mujeres tienen menos de 8 años de escolaridad; los factores que llevaron a las mujeres a retirarse de la escuela incluyen el quedar embarazadas, la necesidad de trabajar para mantenerse y la adherencia a los roles de género tradicionales 8 .…”
Section: Dimensión Psicosocialunclassified
“…The better level of education, measured in years of study, among the participants with high capacity for childcare proved to be an important factor that can interfere directly in the family caregiver's better understanding of the needs of a child exposed to HiV. The low instructional level reflects in limited maternal access to VT instructional preventive measures, as shown in a retrospective documentary study conducted in medical records of 110 mothers with HiV and their children (20).…”
Section: Response To Pharmacological and Clinical Compliance Monitoringmentioning
confidence: 99%